Extended digital image correlation method for analysis of discrete discontinuity. (November 2015) - Deb, Debasis; Bhattacharjee, Sudipta
Abstract: Finite element based multilevel extended digital image correlation (X-DIC) method is applied to obtain displacement distribution of an object having a discrete discontinuity. The principle of multilevel X-DIC method is described in the paper and results are verified using numerically generated images. The deformed images are developed with a pre-existing discontinuity surface across the image for tensile or shear displacements or rotations. Several cubical rock samples are also compressed under uniaxial loading conditions until fractures are developed in the post-failure region. Images of a speckled face of this experiment are analyzed using the proposed X-DIC method with increment of loading for determination of displacement before and after cracks are developed in the sample. The results of this study show that X-DIC technique is capable of capturing damaged zone(s) and displacement jump across the discontinuity plane as well as indicating the onset of failure of rock sample. This method demonstrates the applicability to investigate object failure mechanism for the entire surface of the sample in a non-contact manner. Abstract : Highlights: Multilevel X-DIC method for displacement distribution of an object having discrete discontinuity The results are verified using numerically generated images. Experimental works are carried out under uniaxial loading conditions. X-DIC technique is capable for indicating the onset of failure of rock sample